Evaluation of Compressive Strength and Sorption/Solubility of Four Luting Cements - Tavangar MS; Jafarpur D; Bagheri R (Shiraz University of Medical Sciences, 2017)
Abstract: Statement of Problem: Compressive strength (CS) and sorption/solubility of the luting cements are two associated factors. Searching a correlation between sorption/solubility and compressive strength of various luting cements is required. Objectives: To measure the water sorption/solubility, and compressive strength of three resin-based and one conventional glass ionomer (CGI) luting cement after 1 and 24 h of immersion in distilled water and to determine if there is any correlation between those properties found. Materials and Methods: Four luting cements were investigated. For each material, 10 disc shaped specimens were prepared for measuring the sorption/solubility. The specimens were cured according to the manufacturer's instructions, and the sorption/solubility were measured in accordance with the ISO 4049's. For testing the compression strength, for each material 16 cylindrical specimens were prepared by insertion of cements into a stainless steel split mould. The specimens were cured, divided into groups of 8, and then stored in distilled water at (37 ± 1)°C for 1 and 24 h. The test was performed using the universal testing machine, the maximum load was recorded and CS was calculated. The data were analysed using SPSS software version 18. One-way ANOVA, post-hoc Tukey's test and Pearson's correlation coefficient were performed. Results: G-CEM had the highest mean CS (153.60± 25.15) and CGI luting had the lowest CS (21.36±5.37) (p <0.001). After 24 h, mean CS values showed an increase for almost all materials except for RelyXTM U200 which showed a slight reduction. However, no statistically significant difference was founded (all p > 0.05). The lowest mean sorption/solubility value was for RelyXTM U200 and Panavia F, and the highest for CGI luting (all p < 0.001). Conclusions: The compressive strength of all cements did not necessarily increase after 24 h and varied depending on the materials. There was a strong reverse correlation between sorption and CS values after both 1 and 24 h immersion. It may be practical for clinician to use those cements with the less sorption / solubility and more stable compression strength over time.